2012
DOI: 10.1371/journal.pone.0030372
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Live-Cell Imaging Analyses of SPA-2, BUD-6 and BNI-1 in Neurospora crassa Reveal Novel Features of the Filamentous Fungal Polarisome

Abstract: A key multiprotein complex involved in regulating the actin cytoskeleton and secretory machinery required for polarized growth in fungi, is the polarisome. Recognized core constituents in budding yeast are the proteins Spa2, Pea2, Aip3/Bud6, and the key effector Bni1. Multicellular fungi display a more complex polarized morphogenesis than yeasts, suggesting that the filamentous fungal polarisome might fulfill additional functions. In this study, we compared the subcellular organization and dynamics of the puta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 89 publications
(121 reference statements)
1
36
0
Order By: Relevance
“…S. cerevisiae formin Bni1 also is required for the de novo assembly of actin filaments and of actin contractile rings in budding yeast , Sagot et al 2002, Tolliday et al 2002, Pring et al 2003. Formin orthologs in A. nidulans (SepA ) and N. crassa (Bni1) also were required for septum formation and localized to septation sites (Sharpless and Harris 2002, Lichius et al 2012, Delgado-Alvarez et al 2014. These studies suggest that the formation of actin contractile rings required de novo-assembled actin filaments in animals and fungi.…”
Section: Discussionmentioning
confidence: 83%
“…S. cerevisiae formin Bni1 also is required for the de novo assembly of actin filaments and of actin contractile rings in budding yeast , Sagot et al 2002, Tolliday et al 2002, Pring et al 2003. Formin orthologs in A. nidulans (SepA ) and N. crassa (Bni1) also were required for septum formation and localized to septation sites (Sharpless and Harris 2002, Lichius et al 2012, Delgado-Alvarez et al 2014. These studies suggest that the formation of actin contractile rings required de novo-assembled actin filaments in animals and fungi.…”
Section: Discussionmentioning
confidence: 83%
“…The fact that addition of NSC23766 does not remove the CRIB reporter from septa, furthermore, suggests that CDC-42 takes the primary role in septation. In a previous study, we have shown that the actin-binding protein BUD-6 becomes recruited to the incipient septation site and, together with the formin BNI-1, remains associated with the leading edge of the constricting actomyosin ring (CAR) (Lichius et al, 2012b). It has been suggested that the CDC-42-RAC-1-CDC-24 module acts as a negative regulator of the septation process, counteracting RHO-1 and RHO-4 which have been positively attributed to septation (Rasmussen and Glass, 2005;Rasmussen and Glass, 2007;JustaSchuch et al, 2010; see also reviews by Seiler and Justa-Schuch, 2010;Mouriño-Pérez and Riquelme, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A similar but so far unknown mechanism might steer tip growth in fusing germlings and hyphae. The Bni1 homolog of N.crassa localizes to sites of cell fusion, is, however, not essential for this process, indicating that other cytoskeleton organizing factors contribute to MAK-2-mediated self-tropism [47].…”
Section: The Mak-2 Map Kinase Cascadementioning
confidence: 97%